2023
DOI: 10.1051/0004-6361/202347142
|View full text |Cite
|
Sign up to set email alerts
|

Solar photospheric spectrum microvariability

Dainis Dravins,
Hans-Günter Ludwig

Abstract: Context. Extreme precision radial-velocity spectrometers enable extreme precision in stellar spectroscopy. Searches for low-mass exoplanets around solar-type stars are limited by various types of physical variability in stellar spectra, such as the short-term jittering of apparent radial velocities on levels of ∼2 m s−1. Aims. To understand the physical origins of radial-velocity jittering, the solar spectrum is assembled, as far as possible, from basic principles. Solar surface convection is modeled with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 145 publications
0
0
0
Order By: Relevance
“…Of the existing suite of high-resolution RV spectrographs, it is most plausible that ESPRESSO (in UHR mode) or PEPSI could resolve the submeters per second stellar line-shape variations that characterize granulation-driven jitter, assuming an adequate number of similarly varying lines can be identified and binned. As discussed in Section 4.3.2, a recent work based on HD simulations (Dravins & Ludwig 2023) demonstrated that subsets of lines do indeed vary in phase, motivating our claim that variability in granulation signals would need to be coherently binned across lines. Line lists derived from or informed by such HD simulations could provide a valuable starting point for observational studies of convective variability in other stars.…”
Section: Overcoming Observational Constraintsmentioning
confidence: 77%
See 2 more Smart Citations
“…Of the existing suite of high-resolution RV spectrographs, it is most plausible that ESPRESSO (in UHR mode) or PEPSI could resolve the submeters per second stellar line-shape variations that characterize granulation-driven jitter, assuming an adequate number of similarly varying lines can be identified and binned. As discussed in Section 4.3.2, a recent work based on HD simulations (Dravins & Ludwig 2023) demonstrated that subsets of lines do indeed vary in phase, motivating our claim that variability in granulation signals would need to be coherently binned across lines. Line lists derived from or informed by such HD simulations could provide a valuable starting point for observational studies of convective variability in other stars.…”
Section: Overcoming Observational Constraintsmentioning
confidence: 77%
“…Some initial work (Dravins et al 2017a(Dravins et al , 2017b has already successfully shown that "similar" Fe lines can be binned in order to enable retrievals of time-averaged spatially resolved stellar line profiles during planet transits. Additionally, HD simulations performed by Dravins & Ludwig (2023) show that different absorption lines fluctuate in phase (with some dependence on line strength and spectral region), suggesting that it is indeed plausible that convective variability can be coherently binned across lines.…”
Section: Practical Considerations For Existing Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation